WHY WE SHOULD CARE ABOUT EVOLUTION AND NATURAL HISTORY: with Peter C. Kjærgaard, "Why We Should Care about Evolution and Natural History"; Kaspar von Greyerz, "Early Modern Protestant Virtuosos and Scientists: Some Comments"; Nathan J. Ristuccia, "Peter Harrison, Ludwig Wittgenstein, and the Problem of Pre‐Modern Religion"; Michael Fuller, "Into Terra Incognita: Charting beyond Peter Harrison's The Territories of Science and Religion"; and Peter Harrison, "The Modern Invention of 'Science‐and‐Religion': What Follows?". Issue 3 (September 2016) - Kjærgaard, Peter C.
Abstract: Historians play it safe. Complex issues are dissected while analytical distance keeps stakeholders at bay. But the relevance of historical research may be lost in caution and failure to engage with a wider audience. We can't afford that. We have too much to offer and too much at stake. We need to take the discussion of science and religion beyond our own professional circles. Peter Harrison's The Territories of Science and Religion gives us an opportunity to do so. We can use his book to understand why people consistently get the relation wrong. However, we need to take the next step ourselves, involve historians in the common academic goal, across disciplines, to make sense of the world around us and make that combined knowledge truly useful. Evolution and natural history might help to that effect.